Pengaruh Efisiensi Modal Kerja Terhadap Rentabilitas Perusahaan Primarasa Food Industry Kediri Pada Tahun 2013 -2017 - Ika Nur Fitriani; Subagyo Subagyo; Mas Wibowo Andoko (CAHAYA AKTIVA, 2019)
Working capital is used to conduct the company's operations. Working capital is defined as investments invested in current assets such as cash, securities, accounts receivable, inventory. in this research is taken two elements of variable working capital elements  of  X1 cash and X2 inventory turnover rate affecting variable Y is rentability. Cash is a tool of exchange and is also used as a measure in accounting, in the balance sheet, cash is a current asset in the sense of frequent change. Almost every transaction with outsiders always affects cash. While the receivable turnover rate is a number that shows how many times a company to bill on receivables in a certain period. Profitability is the company's ability to generate profits. The purpose of this study is to determine whether the cash ratio and receivable turnover rate affect the profitability of Primarasa Food Industry Kediri. The financial statements used in this study are income statement and balance sheet in 2013 up to 2017. Analyze techniques are used by using correlation analysis, multiple linear regression and t test. Regression test results that as described in this research, it can be said that empirically found that the cash ratio has a positive effect on corporate profitability means the higher the cash ratio achieved then increase the profitability of PT Primarasafood (SAWI). It can be proved by regression test result that sig value for influence of X1 (cash ratio) to Y (rentability) is 0,002 <0,05 and Thitung value 22.053> Ttabel 4,303 In this case it is clear that inventory turnover has no effect on the firm's profitability. In the results if the data using SPSS 16.0 for Windows above can be seen that the two independent variables simultaneously affect the dependent variable, where the table 4.5 F value counted 844,299 (F table = 9.55) and the significance level of 0.001 (sig α < 0.05). So generally it can be concluded that the independent variable cash and receivable turnover rate simultaneously affect the dependent variable that is the profitability of Primarasa Food Industry Kediri.Keywords: Working Capital (Cash & Receivable Turnover Rate), Profitability.